PERBANDINGAN MANAJEMEN PEMBELAJARAN TAHFIDZ AL-QUR’AN DI SDN 28 LUNDANG, SMPN 7 BUKITTINGGI, SDN 12 KUOK III KOTO - Humaira , Fadhila; Insannia, Maghfirah; Irawati, Deni; Kurnia, Tuti; Ananda, Arifan; Ilmi, Darul (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Memorizing the Qur'an or reciting the Qur'an is a very noble task both for humans and for the great Almighty Allah. And not everyone is able to do it except people who have a strong desire or istiqamah. And this strong desire must be applied to daily activities without giving up until he truly achieves what he wants, namely to become a muhafidz muhafidzah. So it can be concluded that to become tahfizd you cannot just have a strong desire or determination, but do it by being sincere and trying to purify your intentions from joy and avoiding sinful acts and always praying to Allah SWT.